The status of GIS teaching in South African secondary schools including an evaluation of free and open source software for geospatial (FOSS4G) using QGIS software and OpenStreetMap (OSM) data as teaching interventions - Fleming, Bridget (My University, 2021)
South Africa is one of only a few countries that has Geographic Information Systems (GIS) in the secondary school curriculum. Of these few, SA is even more singular as its Geography syllabus includes GIS geoprocessing. The status of GIS teaching in secondary schools is investigated with the aim to determine if the use of Open Source software and data such as QGIS and OSM would facilitate the use of GIS as a teacher intervention. The data was collected by means of an online questionnaire and a smaller sample was interviewed. Results from this study show that only a minority of teachers teach practical GIS classes irrespective of their Examination Board, access to hardware, how resourced their school is or whether they teach at a private or a government school. The key determinants to teaching practical GIS lessons are the teacher’s perceived GIS expertise and access to GIS data and time. Software, connectivity, and power supply were also identified as challenges. Teachers who participated in the study overwhelming agree that there are numerous benefits to using GIS in the classroom. They also expressed a keen willingness to attend GIS courses and learn more about FOSS4G tools. A sample group evaluated how OSM could be used to create local GIS spatial data and how QGIS can be used to teach the GIS curriculum and used to map local data for individual research projects. FOSS4G empowers teachers with the means to create exciting, real, and relevant teaching content that can be used on all platforms, especially in online teaching, if required. There is an urgent need for more current research, both globally and locally, into how GIS can be used more in secondary school pedagogy.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, School of Geography, Archaeology and Environmental Studies, University of the Witwatersrand, Johannesburg, 2021
Keywords: Geographic information systems-Study and teaching; Teachers-South Africa